Серебряная лодка: Стихи и поэмы: Пер. с удм. / Николай Байтеряков - Байтеряков Николай Семенович (Удмуртия, 1989)
Экземпляры: (20180626) / Инвентарный номер: 24655 / Цена: 1.00 / Сис.шифр: С / Авт.знак: Б18 / ББК: С(Удм)